2021
DOI: 10.1093/infdis/jiab104
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Attenuated Transmissibility of SARS-CoV-2 in Domestic Cats

Abstract: Domestic cats, an important companion animal, can be infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This has aroused concern regarding the ability of domestic cats to spread the virus that causes coronavirus disease 2019. We systematically demonstrated the pathogenesis and transmissibility of SARS-CoV-2 in cats. Serial passaging of the virus between cats dramatically attenuated the viral transmissibility, likely owing to variations of the amino acids in the receptor-binding domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
93
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 22 publications
5
93
0
2
Order By: Relevance
“…Pair-transmission experiments are a suitable design to assess transmission. By using both data from the studies that used this type of experimental design (10,14) and data from studies which followed infected households, we statistically confirmed that sustained transmission of SARS-CoV-2 among cats can be expected (R 0 > 1). To put this into perspective, scenarios in which contacts between stray and household cats take place (3) could lead to persistence of the virus in the cat population.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Pair-transmission experiments are a suitable design to assess transmission. By using both data from the studies that used this type of experimental design (10,14) and data from studies which followed infected households, we statistically confirmed that sustained transmission of SARS-CoV-2 among cats can be expected (R 0 > 1). To put this into perspective, scenarios in which contacts between stray and household cats take place (3) could lead to persistence of the virus in the cat population.…”
mentioning
confidence: 59%
“…The role of cats is of particular interest, because they are in close contact with humans and frequently in contact with other cats. Available field (2)(3)(4)(5)(6)(7)(8)(9) and experimental data (10)(11)(12)(13)(14) indicate that cats are susceptible to infection, occasionally show mild clinical signs and may be able to transmit the infection between cats. Indeed, transmission experiments confirmed this possibility (10)(11)(12)(13)(14), however, the lack of a proper statistical assessment of transmission in the reported experiments limits confident extrapolation of the results from the experiment to the population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have also identified that the transmissibility of SARS-CoV-2 is dramatically attenuated upon serial passaging in cats (via one-to-one homosexual cohousing of an infected cat with a naive cat). The cat-to-cat transmissibility of SARS-CoV-2 was found to be reduced over time in cats as compared to the sustained human-to-human transmission (Bao et al 2021). This can be attributed to the variations existing in the binding sites of feline ACE2 receptor as compared to human beings (Bao et al 2021).…”
Section: Sars-cov-2 In Domestic Animals and Feral Carnivoresmentioning
confidence: 98%
“…The cat-to-cat transmissibility of SARS-CoV-2 was found to be reduced over time in cats as compared to the sustained human-to-human transmission (Bao et al 2021). This can be attributed to the variations existing in the binding sites of feline ACE2 receptor as compared to human beings (Bao et al 2021). In addition to that, cats previously infected with SARS-CoV-2 were found to be susceptible to reinfection in the subsequent experimental inoculation.…”
Section: Sars-cov-2 In Domestic Animals and Feral Carnivoresmentioning
confidence: 98%